الكلام البلاغي لعلم المعاني وفوائده في سورة الحاقة - Ahmad Nuruddin (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2022)
This study aims to know the rhetorical discourse of semantics and its benefits in Surat Al-Haqqa. The rhetorical speech is divided into the predicate, constructive, and predicate in Surat Al-Haaqah. The researcher found 34 primaries, requesting, negative, and constructive words in Surat Al-Haaqqa. The benefits of declarative and compositional speech consist of natural and rhetorical benefits. The problems discussed in this research are: 1) What are the types of rhetorical speech in Surat Al-Haqqah? 2) What are the benefits of rhetorical speech in Surat Al-Haqqah? The researcher used the research tools: observation, discussion, and analysis